Gender-differences in antithrombotic therapy across the spectrum of ischemic heart disease: Time to tackle the Yentl syndrome? - Laborante, Renzo; Borovac, Josip Andjelo; Galli, Mattia; Rodolico, Daniele; Ciliberti, Giuseppe; Restivo, Attilio; Cappannoli, Luigi; Arcudi, Alessandra; Vergallo, Rocco; Zito, Andrea; Princi, Giuseppe; Leone, Antonio Maria; et al. (Frontiers in Cardiovascular Medicine, 2022)
The incidence and clinical presentation of ischemic heart disease (IHD), as well as thrombotic and bleeding risks, appear to differ between genders. Compared with men, women feature an increased thrombotic risk, probably related to an increased platelet reactivity, higher level of coagulation factors, and sex-associated unique cardiovascular risk factors, such as pregnancy-related (i.e., pre-eclampsia and gestational diabetes), gynecological disorders (i.e., polycystic ovary syndrome, early menopause) and autoimmune or systemic inflammatory diseases. At the same time, women are also at increased risk of bleeding, due to inappropriate dosing of antithrombotic agents, smaller blood vessels, lower body weight and comorbidities, such as diabetes and chronic kidney disease. Pharmacological strategies focused on the personalization of antithrombotic treatment may, therefore, be particularly appealing in women in light of their higher bleeding and ischemic risks. Paradoxically, although women represent a large proportion of cardiovascular patients in our practice, adequate high-quality clinical trial data on women remain scarce and inadequate to guide decision-making processes. As a result, IHD in women tends to be understudied, underdiagnosed and undertreated, a phenomenon known as a “Yentl syndrome.” It is, therefore, compelling for the scientific community to embark on dedicated clinical trials to address underrepresentation of women and to acquire evidence-based knowledge in the personalization of antithrombotic therapy in women.